Universal health coverage necessitates a system approach: an analysis of Community-based Health Planning and Services (CHPS) initiative in Ghana - Abraham Assan; Amirhossein Takian; Moses Aikins; Ali Akbarisari (BMC, 2018)
Abstract The 9th Global conference on health promotion (Shanghai 2016) reaffirmed the role of primary health care (PHC) in achieving the 2030 Sustainable Development Agenda. Gaining much international recognition, the community-based health planning and services (CHPS) initiative is considered one of the pragmatic strategy in delivering on the promise of universal health coverage (UHC) through the PHC strategy, in Ghana. Yet, certain key factors threaten its successes - renewing the relevance of this study to present the barriers to and facilitators of the initiative. According to our findings, CHPS contribution particularly in bridging geographical access to health cannot be demeaned. Nevertheless, the full functioning of the initiative is limited by factors centered on the following themes: health governance and leadership, provision of services of quality, financial risk protection strategies targeting public health, information and care continuity, and the right mix of trained health professionals of even distribution across communities. Addressing the challenges of CHPS demand a system-approach. Substantial progress is more likely to emerge with improved leadership especially on the part of Governments to take bold political step to provide adequate financial and material resources. However, much will be achieved when stakeholders including the community work in synergies, to manage competing priorities by focusing on the core values and goals of CHPS.